Synthesis strategies for graphene - Kumar R.; Singh R.K.; Singh D.P. (My University, 2025)
Since the groundbreaking discovery of a new member of the family of carbon nanostructures, namely, "graphene," discovered by A.K. Geim and K.S. Novoselov in 2004, its widespread applications in various areas further accelerated the research activity in the area of synthesis and characterization of graphene by simple, viable, and low-cost techniques. Graphene, one-atom-thick two-dimensional planar sheets of sp2-bonded carbon atoms densely packed in a honeycomb crystal lattice, has grabbed appreciable attention due to its extraordinary chemical and physical properties. These properties reveal high planar surface area, superior mechanical strength with unparalleled thermal conductivity, remarkable electronic properties, and alluring optical characteristics. Moreover, because of these unique properties, graphene has attracted increasing interest, and, arguably, holds the greatest promise for implementation into a wide range of application fields that include electronic, field emission, energy, biophysics, sensing, and engineering outlets. Ever since, the growing profound interest in the applications of graphene in almost all recent research areas demands the synthesis of graphene of a desired size and purity, which is defect free, and produced which possesses crystallinity and high yield. Since the discovery of graphene by mechanical cleavage, various other methods have been developed so far to fulfill the above requirements. The most common graphene synthesis approaches to produce suitable graphene layers mainly include mechanical exfoliation from graphite, reduction of graphene oxide, chemical vapor deposition, surface segregation, liquid-phase exfoliation, and molecular beam epitaxy. All the methods have their benefits and limitations. The fine control of the defect-free structure and number of graphene layers over an entire substrate remains a major and crucial challenge. Hence, the search to optimize the manufacturing process with a view to the realization of distinct properties of graphene layers is ongoing. This chapter describes the recent advances in the well-known synthesis routes using hydrocarbons, substrates, and optimizing temperatures. The synthesis of graphene by mechanical cleavage and chemical exfoliation by introducing small molecules has been described. The synthesis of graphene by the chemical reduction of obtained graphite oxide by Hummers' method using various reducing agents has been widely studied and extensively utilized. The chemical vapor deposition method utilizing various metals and transition metals as substrate and their effect on the synthesis, yield, and purity have been described in detail. Besides, other effective and well-known methods such as flame synthesis, electrochemical approach, microwave/solvothermal methods, flame synthesis, etc. are also a part of the discussion. © 2016 by Taylor & Francis Group, LLC. All rights reserved.